Preparing for the workplace : charting a course for federal postsecondary training policy - Hansen, Janet S.; National Research Council (U.S.). Committee on Postsecondary Education and Training for the Workplace; National Research Council (U.S.). Commission on Behavioral and Social Sciences and Education (Washington, D.C. : National Academy Press, 1994)
Examines the division of training responsibility between public & private sector. Emphasis on what federal government can & can not do.
Includes bibliographical references (pages 177-193) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Career education -- Government policy -- United States; Postsecondary education -- United States; Federal aid to higher education -- United States; Labor supply -- Effect of education on; Préparation à une carrière -- Politique gouvernementale -- États-Unis.; Enseignement postsecondaire -- États-Unis.; Aide de l'État à l'enseignement supérieur -- États-Unis.; Marché du travail -- Effets de l'éducation sur; EDUCATION -- Higher; Enseignement supérieur.; Formation professionnelle; Politique de formation; Relation formation-emploi.; Etats-Unis d'Amérique.; Career education -- Government policy; Federal aid to higher education; Labor supply -- Effect of education on; Postsecondary education; United States; Berufsbildungspolitik; Tertiärbereich; USA